Study of liquid fertilizer production through complex systems - Saydullaeva Gulnoz Anorboyevna; Tursunov Djakhongir Husanovich; Abdullayeva Marguba Tolibjanovna (Zien Journals, 2024)
Currently, all over the world, with intensive population growth, a reduction in suitable land resources and water reserves, the role of the production of new types of fertilizers is increasing to fully satisfy the population’s needs for quality products. One of the effective ways to produce mineral fertilizers is to obtain them in liquid form. The production of such fertilizers leads to a reduction in a number of processes and, compared to solid fertilizers, to a noticeable reduction in costs.
Keywords: solid fertilizers; production of new types of fertilizers